Mechanical circulation support of the treatment for children with end-stage chronic heart failure - S. V. Gautier; G. P. Itkin; O. Yu. Dmitrieva; V. A. Kozlov (Вестник трансплантологии и искусственных органов)
Over the last decades mechanical circulation support has become one of the most effective treatment methods for patients with terminal heart failure. Unfortunately, in pediatrics this method is generally used on a short-term basis and includes, first of all, extracorporeal membranous oxygenation and left ventricular bypass by means of the extracorporeal centrifugal pumps. Nevertheless, using of these methods in children allowed considerably reducing mortality on the waiting list for heart transplant. Today, practically the only method of long term mechanical circulatory support in newborns and children at an early age being used is the system of paracorporeal artificial ventricles EXCOR, the usage of which results in larger problems of thrombosis. There is little clinical experience in using of the fully implanted systems developed for adults in older children. Therefore, as shown in the present review, the problem of creating long term circulatory support systems for newborns and younger children on the basis of the implanted pumps continues to be relevant.